2017
DOI: 10.1101/211896
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic and environmental determinants of stressful life events and their overlap with depression and neuroticism

Abstract: word count : 249Article word count: 3912 Tables: 5 peer-reviewed) is the author/funder. All rights reserved. No reuse allowed without permission. Number ofThe copyright holder for this preprint (which was not . http://dx.doi.org/10.1101/211896 doi: bioRxiv preprint first posted online Oct. 31, 2017; AbstractBackground: Stressful life events (SLEs) and neuroticism are risk factors for major

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
1
6
0
1
Order By: Relevance
“…However, importantly, both genetic influences and adoption explain only a small part of individual differences in mental health on the population level, and the difference in genetic risk between adoptees and nonadoptees explained only a small fraction of the adoption effect. Our findings are in line with two recent studies using self-reported trauma measures reporting a small but significant association between major depression PRSs and childhood trauma (21) and between the PRSs for major depression and neuroticism with recent SLE exposure, respectively (36). However, the majority of studies exploring main effects of genetic risk and SLE exposure and their interaction on mental health outcomes did not assess potential gene-environment correlations [e.g., (24,37)].…”
Section: Genetic Differencessupporting
confidence: 89%
“…However, importantly, both genetic influences and adoption explain only a small part of individual differences in mental health on the population level, and the difference in genetic risk between adoptees and nonadoptees explained only a small fraction of the adoption effect. Our findings are in line with two recent studies using self-reported trauma measures reporting a small but significant association between major depression PRSs and childhood trauma (21) and between the PRSs for major depression and neuroticism with recent SLE exposure, respectively (36). However, the majority of studies exploring main effects of genetic risk and SLE exposure and their interaction on mental health outcomes did not assess potential gene-environment correlations [e.g., (24,37)].…”
Section: Genetic Differencessupporting
confidence: 89%
“…Smaller studies on genetic determinants of stressful life events showed a significant and robust genetic association between stressful life events and depression. 58 Despite these correlations, the genetic 707 708 709 710 711 712 713 714 715 716 717 718 719 720 721 722 723 724 725 726 727 728 729 730 731 732 733 734 735 736 737 738 739 740 741 742 743 744 745 746 747 748 749 750 751 752 753 754 755 756 757 758 759 760 761 762 763 764 765 studies of response to stress-related events are not uniform, with various different triggers being investigated. Each individual trigger study is much smaller than the large, relatively uniform studies of depression, thus supporting our use of depression as the best proxy for stress to run the most powered genetic correlation analyses possible.…”
Section: Discussionmentioning
confidence: 99%
“…However, the now established genetic overlap between stressful life events and major depressive disorder suggests that their relationship may not be directionally causal but a consequence of common genetic effects that influence both. 47 Nonetheless, most of the stressors in the checklist we used are likely independent events (i.e., beyond the control of the child); the genetic overlap between major depressive disorder and independent life events is lower than for dependent life events 47,48 (such as relationship problems or job loss, that may be, in part, the result of a person's own behaviour).…”
Section: Discussionmentioning
confidence: 99%